Catalyst nucleation and carbon nanotube growth from flame-synthesized Co-Al-O nanopowders at ten-second time scale. (April 2017) - Shirae, Hiroyuki; Hasegawa, Kei; Sugime, Hisashi; Yi, Eongyu; Laine, Richard M.; Noda, Suguru
Abstract: Flame-synthesized (CoO) x (Al2 O3 )1- x spinel nanopowders with primary particles of ∼20 nm were used to grow small diameter carbon nanotubes (CNTs). The nanopowders with x  ≤ 0.35 grew few CNTs whereas that with x  = 0.65 grew CNTs efficiently. Low crystalline and large-diameter multi-wall CNTs grew by annealing and chemical vapor deposition (CVD) at 800 °C for ∼10 min, whereas single-wall CNTs with high crystallinity (G-band to D-band intensity ratio of 20–100 by Raman spectroscopy) grew by annealing and CVD at ≥1000 °C for ∼10 s. The excess Co in the spinel reduced and segregated to form multiple Co nanoparticles on the surface of the single primary alumina nanoparticles in ∼10 s, yielding SWCNTs in ∼10 s. Such flame synthesized nanopowders, reduced and activated by H2, provide CNTs from C2 H2, all in ten-second time scale, and as such are promising for practical, high-through-put production of small-diameter CNTs. Graphical abstract: